Entropy analysis in thermal engineering systems - Haseli, Yousef (Academic Press, 2020)
Entropy Analysis in Thermal Engineering Systems is a thorough reference on the latest formulation and limitations of traditional entropy analysis. Yousef Haseli draws on his own experience in thermal engineering as well as the knowledge of other global experts to explain the definitions and concepts of entropy and the significance of the second law of thermodynamics. The design and operation of systems is also described, as well as an analysis of the relationship between entropy change and exergy destruction in heat conversion and transfer. The book investigates the performance of thermal systems and the applications of the entropy analysis in thermal engineering systems to allow the reader to make clearer design decisions to maximize the energy potential of a thermal system. --